Analisis Pengaruh Kualitas Harga dan Kualitas Pelayanan terhadap Kepuasaan Pelanggan (Studi Kasus Shopee) - Rahmawati, Devi; Rahmawati, Devi Arina; Handayani, Popon (Jurnal Sistem Informasi Akuntansi, 2024)
Changes in communication technology that are very fast have brought extraordinary changes. Offline trading patterns are starting to shift to online business. It can be seen that in the shopee comments or reviews column there are still various complaints from customers indicating that customer satisfaction on the shopee side is still too low. Price is the first reason shopee customers buy the items they want. Service quality is also a consideration for shopee customers. Shopee must provide excellent and satisfying service to customers. With the aim of research to find out how much price quality and service quality affect customer satisfaction in shopee users. The data were processed in this study using an associative method with a quantitative approach. With the results of the calculation of the validity test each obtained a value of r count> r table at a significant value of 5% or 0.195. And the results of the reliability test each obtained a Cronbach's alpha value of 0.705, which was greater than the r table value of 0.195. The results of the classic assumption test, namely the normality test, multicollinearity test, and heteroscedasticity test each state that it is feasible to be used as a benchmark. The results of the t test on the price quality variable obtained a significant value of 0.055 <0.05, so partially there is a positive effect of price quality on customer satisfaction. The results of the f test on the price quality variable, service quality obtained a sig value of 0.000 <0.05, so simultaneously there is a positive influence on customer satisfaction. The results of r square show the value (r square) obtained from the study of 0.237. The r square results mean that 23.7% of the variation in customer satisfaction is influenced by the two variables, namely price quality and service quality. While the remaining 76.3% is influenced by other causes outside the model.